An investigation on bloom dynamics of Alexandrium catenella and A. pacificum and toxin accumulation in shellfish along the coast of Qinhuangdao, China. (October 2022) - Tang, Wen-Jiao; Lin, Zhuo-Ru; Zhang, Qing-Chun; Geng, Hui-Xia; Sun, Hong-Xiao; Tang, Xue-Xi; Yu, Ren-Cheng
Abstract: The dinoflagellate genus Alexandrium comprises most of the toxic bloom-forming species producing paralytic shellfish toxins (PSTs) in the sea. Recently, repeated paralytic shellfish poisoning episodes have been recorded in Qinhuangdao located at the west coast of the Bohai Sea. To elucidate the relationship between toxic Alexandrium blooms and the poisoning episodes, a year-round investigation was carried out in this region from July 2020 to July 2021. Two qPCR assays were used to detect A. catenella and A. pacificum, and LC-MS/MS was applied to analyze PSTs in phytoplankton and shellfish samples. The blooms of A. catenella and A. pacificum were found in April and July, respectively, and PST content in three bivalves exhibited notable increase following the bloom of A. catenella . The results revealed bloom dynamics of the two toxic Alexandrium species in the Bohai Sea for the first time, and further confirmed A. catenella as the causative agent of poisoning episodes. Highlights: Toxic Alexandrium and paralytic shellfish toxins were studied in Qinhuangdao, China. catenella bloomed in April and A. pacificum bloomed in July based on qPCR assay. Toxin content in bivalves had notable increase following the bloom of A. catenella . catenella was confirmed as causative agent for poisoning episodes in this region.